DiaSim: a simulator for pervasive computing applications‡. (14th May 2012) - Bruneau, Julien; Consel, Charles
SUMMARY: Pervasive computing applications involve both software concerns, such as any software system, and integration concerns, for the constituent networked devices of the pervasive computing environment. This situation is problematic for testing because it requires acquiring, testing, and interfacing a variety of software and hardware entities. This process can rapidly become costly and time‐consuming when the target environment involves many entities. This paper introduces DiaSim, a simulator for pervasive computing applications. To cope with widely heterogeneous entities, DiaSim is parameterized with respect to a description of a target pervasive computing environment. This description is used to generate both a programming framework to develop the simulation logic and an emulation layer to execute applications. Furthermore, a simulation renderer is coupled to DiaSim to allow a simulated pervasive system to be visually monitored and debugged. DiaSim has been implemented and used to simulate various pervasive computing systems in different application areas, demonstrating the generality of our parameterized approach. Copyright © 2012 John Wiley & Sons, Ltd.